DO REALLY EMOTIONAL QUOTIENT AND SPIRITUAL QUOTIENT AFFECT ON EMPLOYEE PERFORMANCE? - Shofia Amin; Nany Mawaddah (Management Department, Faculty of Economics and Business, Universitas Jambi, 2017)
The main purpose of this study is to examine the effect of emotional quotient on work performance, and the effect of spiritual quotient on work performance at BPMPPT of Jambi City. Using 68 employees as respondent, the data were collected by distributing questionnaire and analyzed by using partial least squares path modeling (PLS-SEM). The results of the analysis show that overall emotional intelligence and spiritual intelligence employee BPMPPT Jambi city is at a high level of quotient. While employee performance BPMPPT Jambi city is at a level of performance was enough. The statistical analysis shows that partially and simultantly emotional quotient and spiritual quotient has significant and positive effect on employee performance. Keywords: Emotional Quotient, Spiritual Quotient, Performance